"Stay sexy and don’t get murdered": depictions of female victimhood in post-Me Too true crime - Hoffman, Megan (Critiquing violent crime in the media, 2021)
This chapter examines the ways in which recent true crime narratives produced by women reflect discourses shaped by the Me Too movement. In the podcast My Favorite Murder with Karen Kilgariff and Georgia Hardstark, Hallie Rubenhold’s book The Five: The Untold Lives of the Women Killed by Jack the Ripper (2019), and documentaries The Yorkshire Ripper Files: A Very British Crime Story (2019) and Ted Bundy: Falling for a Killer (2020), women’s voices and perspectives are centred in ways that significantly question how female victimhood is represented, both in true crime and within wider cultural contexts. However, while these texts can be seen to challenge the true crime genre’s conventions, they also fail to fully escape those conventions, at times reaffirming problematic discourses that erase or exploit victims.